2s+2(s+2)=4(s+2)-4

Simple and best practice solution for 2s+2(s+2)=4(s+2)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2s+2(s+2)=4(s+2)-4 equation:


Simplifying
2s + 2(s + 2) = 4(s + 2) + -4

Reorder the terms:
2s + 2(2 + s) = 4(s + 2) + -4
2s + (2 * 2 + s * 2) = 4(s + 2) + -4
2s + (4 + 2s) = 4(s + 2) + -4

Reorder the terms:
4 + 2s + 2s = 4(s + 2) + -4

Combine like terms: 2s + 2s = 4s
4 + 4s = 4(s + 2) + -4

Reorder the terms:
4 + 4s = 4(2 + s) + -4
4 + 4s = (2 * 4 + s * 4) + -4
4 + 4s = (8 + 4s) + -4

Reorder the terms:
4 + 4s = 8 + -4 + 4s

Combine like terms: 8 + -4 = 4
4 + 4s = 4 + 4s

Add '-4' to each side of the equation.
4 + -4 + 4s = 4 + -4 + 4s

Combine like terms: 4 + -4 = 0
0 + 4s = 4 + -4 + 4s
4s = 4 + -4 + 4s

Combine like terms: 4 + -4 = 0
4s = 0 + 4s
4s = 4s

Add '-4s' to each side of the equation.
4s + -4s = 4s + -4s

Combine like terms: 4s + -4s = 0
0 = 4s + -4s

Combine like terms: 4s + -4s = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x+(-17)=1 | | x*(x+1)/2=453 | | -2y=-8x | | (1/4)-(5/y)=3 | | 7y+4(y-6)=4(y+2)-5 | | p(x)=3x^4-4x^3+x^2+6x-2 | | -2d+8=2(-d+4) | | 3.6x+14.7=.3-1.2x | | .3x+8.6=.65x+10 | | 13-20-(-2)= | | y=-4x^5+2x^4+6x+5 | | 25-2(7+5)= | | 36+35/5*4 | | 4(c-3)-6=6 | | -7(x+2)-18=25+6 | | 141/9-13/18 | | .4+.6x=.53+.5x+1.5 | | 3x^4-4x^3+x^2+6x-2= | | 2x+y=-400 | | -(1-2)-4= | | y=-3x^9+8x^6+7x^5+7 | | w=p(v-l) | | 8-(11-7)= | | 5/9+10 | | (4w-9)(5-w)=0 | | 9-3(-2-5)=30 | | 6m-8=2+9m-11 | | 2(z-1)=4(z+5)-10 | | 5(y-7)/4=-2y | | 2.4x=-8.4 | | 3x-5x=20 | | 1/4x-5=-25 |

Equations solver categories